Prowadzenie badań naukowych jako podstawa żądania udzielenia informacji publicznej - Jakubowski, Aleksander (Kwartalnik Prawa Publicznego, 2012)
It is currently assumed, that conducting scientific research is private sphere. Therefore, it can’t be regarded as significant for public. This view is presented in court decisions and literature. A comprehensive analysis indicates that this view is too radical. Systemic analysis of law shows that the conducting research is considered as significant for society, for the public interest. This is also confirmed by the results of functional interpretation. However, to get processed public information it must be shown, that public interest is „especially important”. This kind of interest will have specialized bodies which conduct publicly funded scientific research for the aims designated by public authorities (government).